Ultrasonographic neasurements of the Achilles tendon thickness of men and women athletes in Olympic weightlifting - Tüfekçi, O.; Erdagi, K. (Journal of Education and Training Studies, 2019)
Objectives: The study aims to investigate the Achilles tendon thickness of men, women athletes in Olympic weightlifting and sedentary individuals.